Innovation of new business models as a guide for academic development in post-COVID-2019 contexts - Fernández Otoya, Fiorela Anaí (2022)
In this paper, a review of different bibliographic sources that have business models, innovation, and academic contributions as research variables in a post-Covid-19 context is presented. The main objective of the article is to provide knowledge to researchers who want more information on concepts, use cases, and relevant information related to business model innovation in academic and business research environments. A rigorous source search was conducted in Scopus, where 19 essential sources were considered for the present review. Different concepts, and cases in a pre and post-Covid 19 context such as “Mejor en Bici” and “La Mar” were analyzed from source to source and finally, several reflections on the contribution of the study of the business model and its constant innovation in the field of academic and business research were found.